SMG9 Serves as an Oncogene to Promote the Tumor Progression via EMT and Wnt/β-Catenin Signaling Pathway in Hepatocellular Carcinoma - Jin, Xing; Yin, Jie; Zhu, Hongling; Li, Weikang; Yu, Kewei; Liu, Miao; Zhang, Xiujuan; Lu, Miaolian; Wan, Zemin; Huang, Xianzhang (Frontiers in Pharmacology, 2021)
Background/Aims: SMG9 participates in the nonsense-mediated mRNA decay process that degrades mRNA harboring nonsense mutations introduced either at the level of transcription or RNA processing. However, little is known about the role of SMG9 in hepatocellular carcinoma (HCC). The objective of this research was to clarify the effects of SMG9 expression on HCC progression. Methods: Microarray data were acquired from NCBI Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) database to bioinformatically analyze the differential expression of SMG9 between HCC patients and normal controls. SMG9 mRNA level was measured in sixteen sets of fresh tumor tissues and adjacent non-cancerous liver tissues (ANLTs) via reverse transcription-quantitative polymerase chain reaction (RT-qPCR). SMG9 protein expression was analyzed in ninety-five sets of paired formalin-fixed and paraffin-embedded tissue specimens by immunohistochemistry (IHC). In addition, clinicopathological features of SMG9 in HCC were checked. For in vitro studies, small interfering RNA (siRNA) was used to silence SMG9 expression for exploring biological functions and underlying mechanisms of SMG9 in SMMC-7721 and HepG2. Results: We found that SMG9 was upregulated in HCC tissues and SMG9 levels were closely related to TNM stage, tumor number and tumor size. Cox regression and Kaplan–Meier proportional hazards analyses showed that high expression of SMG9 was associated with poor patient survival. Furthermore, proliferation, apoptosis resistance, migration and invasion of both SMMC-7721 and HepG2 cells were suppressed by SMG9 inhibition. In addition, EMT and the Wnt/β-catenin signaling pathway were involved in SMG9-mediated HCC progression. Conclusions: SMG9 may serve as a potential novel prognostic biomarker and therapeutic target in HCC patients.